Demographic Bonus to Support Economic Growth in Indonesia - Safina Meilia (Eduvest - Journal of Universal Studies, 2025)
In Indonesia, the demographic bonus is an ongoing phenomenon with the peak expected to occur in 2030. This phenomenon can have a positive impact with an increase in labor supply and the potential of the community to save, on the other hand, the increasing population makes the needs of the community more and more. This study aims to determine the effect of demographic bonus on growth and how much growth prospects can occur in the future. The research method used is OLS time series data from 1986-2020. The results show that the TO, Population aged 15-64 and Unemployment variables significantly affect GDP growth. Meanwhile, the TPAK and GCF variables are not significant. From this, forcasting Indonesia's economic growth shows a downward trend if the government does not immediately form appropriate policies in dealing with this problem.